(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
In this interview with the professor and set designer José Luiz Valles Ruiz, from the city of Lima, Peru, we propose to present an action carried out at the A Luz em Cena Event 11th edition of 2023. In it we intend to create a behind-the-scenes tour of the scenography, transforming spaces and transmitting knowledge, from his initial knowledge as an academic and then as an independent set designer, researcher in higher schools in other countries and his return as a theater teacher, set design area at ENSAD, National Higher School. of Dramatic Art located in the city of Lima, capital of Peru.